Stent-induced compression necrosis for the endoscopic removal of a partially eroded Lap-Band. (13th June 2018) - Talib, Ali; de Ridder, Rogier; Straathof, Jan Willem; Bouvy, Nicole D
Abstract : Endoscopic removal of eroded Lap-Bands is a minimally invasive alternative to surgical removal that prerequires sufficient erosion through the gastric wall, that is, ≥180° of the gastro-oesophageal wall circumference. A 69-year-old woman presented with dysphagia due to a long-standing Lap-Band erosion, currently of a 60° circumference. Adhesions due to her extensive surgical history rendered surgical treatment undesirable, so a self-expanding stent was placed endoscopically to induce sufficient erosion for subsequent endoscopic removal. During therapy, the patient complained of ructus and dysphagia, probably related to an overly proximally (oesophageal) positioned stent. After a total of 12 weeks, far longer than the described stenting duration in the literature, the Lap-Band was found free in the gastric lumen and was successfully removed using an endoscopic loop. Stent-induced compression necrosis should be considered as a minimally invasive treatment option for Lap-Bands eroded for <180°, with caution in the context of extensive fibrosis.